Building Abe's Personal Brand Through TikTok Content Strategy: Membangun Merek Pribadi Abe Melalui Strategi Konten TikTok - Amru, Muhammad Nafis Ilyasa’; Rochmaniah, Ainur (Universitas Muhammadiyah Sidoarjo, 2025)
Building a personal brand is crucial for enhancing one's visibility and establishing a good reputation. This study aims to identify the strategies employed by content creators in building Abe's personal brand on the TikTok social media platform. The research method used in this study is qualitative descriptive. Data was collected using content analysis techniques on the TikTok account @abe_daily. The results of this study found that Benny has successfully built Abe's personal brand as a funny and active child while interacting with his followers. This also indicates that Benny, as Abe's father, has implemented good parenting practices, as demonstrated by Abe's development as a healthy and active toddler. Highlights: Benny successfully builds Abe's personal brand as a funny, active child. Content strategy focuses on interaction with followers to enhance engagement. Parenting practices are reflected in Abe's development as a healthy toddler. Keywords : Personal Branding, Media Sosial, Tiktok, @Abe_Daily